Penerapan Dutch Angle Dalam Enggambarkan Emosional Pada Film “Tolong Aku” - Nazarruddin Nazarruddin; Dani Manesah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Film, as a genre in the world of cinema, offers a short but captivating audiovisual experience. Films have the potential to create creative, entertaining works and have high artistic value. In the filmmaking process, various techniques and elements are used to improve the quality of the final result. Films are able to convey messages and emotions through various means, including dialogue, visuals, music and special effects. This research focuses on the important role of shooting techniques or cameras in film making. One of the techniques taught is Dutch Angle or Dutch Tilt, which involves tilting the camera angle on a vertical or horizontal axis. This technique is often used in the thriller and horror genres to create a dramatic effect on the audience. The film